Rethinking the Palestinians Abroad as a Diaspora: The Relationships between the Diaspora and the Palestinian Territories - Hanafi, Sari (Hagar: Studies in Society and Culture, 2003)
This article raises a series of questions regarding the taxonomy employed to understand the Palestinians living abroad, their identity, and their relationships to both the homeland and their host societies. For many reasons, the literature on Palestinians has extensively used the term “Palestinian refugees” and considers other notions, such as “diaspora,” “forced and volunteered migrants,” or “Palestinians abroad,” as inadequately stating or weakening the defense or “the cause ” of this population. Moreover, the relationship between this population and the Palestinian territories, or historic Palestine, is supposed to be ‘natural’ and ‘primordial’. This article proceeds as follows. The problematic issue of Palestinians abroad is first debated within the general trends of migration studies. The concept of “diaspora” is then examined in detail, particularly since it privileges as well as emphasizes the relationships with the country of origin as a major element in the web of relationships that the forced migrants are able to establish. I then go on to argue that the Palestinians abroad do not constitute a real diaspora, but rather a “partially diasporized people”. This is then examined by constructing a typology of three ideal-types: diasporized people, population in transit, and assimilated population. Finally, I develop an explicative model of the ongoing and unachieved diasporazation of the Palestinian people. This model is based on two central points: the weak and fragile center of gravity of the Palestinian diaspora, and the recent crystallization of a Palestinian identity.